Time Horizon And Uncovered Interest Parity In Emerging Economies - Sarmidi, Tamat; Mohd Salleh, Norlida Hanim (Asian Academy of Management (AAM), 2011)
The aim of this study is to re-examine the well-known empirical puzzle of uncovered interest parity (UIP) for emerging market economies with different prediction time horizons. The empirical results obtained using dynamic panel and time series techniques for monthly data from January 1995 to December 2009 eventually show that the panel data estimates are more powerful than those obtained by applying individual time series estimations and the significant contribution of the exchange rate prediction horizons in determining the status of UIP. This finding reveals that at the longer time horizon, the model has better econometric specification and thus more predictive power for exchange rate movements compared to the shorter time period. The findings can also be a signalling of well-integrated currency markets and a reliable guide to international investors as well as for the orderly conduct of monetary authorities.